Proceedings of the 2008 ACM Conference on Computer Supported Cooperative Work 2008
DOI: 10.1145/1460563.1460668
|View full text |Cite
|
Sign up to set email alerts
|

An examination of daily information needs and sharing opportunities

Abstract: A person often has highly context-sensitive information needs that require assistance from individuals in their social network. However, a person"s social network is often not broad enough to include the right people in the right situations or circumstances who can satisfy the needs. The ability to satisfy context-sensitive information needs depends on a person"s ability to seek the answers from appropriate individuals, who must then provide a response in a timely manner. To gain an understanding of how to bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 26 publications
3
55
0
1
Order By: Relevance
“…These categories have been individually used by other researchers O'relly and Helen [55,57]. This action, the grouping of information behaviour dimensions, is consistent with the practice of other researchers [60][61][62].…”
Section: Measurementmentioning
confidence: 62%
“…These categories have been individually used by other researchers O'relly and Helen [55,57]. This action, the grouping of information behaviour dimensions, is consistent with the practice of other researchers [60][61][62].…”
Section: Measurementmentioning
confidence: 62%
“…Some of the contextual needs that we found are covered by the topical list of information needs generated by prior work [21,6,11,3]. The larger overlap falls within the spatiotemporal category.…”
Section: Discussionmentioning
confidence: 85%
“…Participants indicated that 72% of their reported information needs were prompted by some contextual factor. In the same year, Dearman et al [6] published the results of a 4-weeks diary study on how information needs can be supported by individuals in the social network. They found that the timeliness of the message and the trust relationship with the source of the answer were variables that participants took into account to evaluate the usefulness of the received information.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Por esta razãoé possível que apresente limitações como o não preenchimento de forma devida pelos participantes. Dearman, Kellar e Truong [28] sugerem algumas estratégias para minimizar estas limitações.…”
Section: Atividade 2 -Estudos Diáriosunclassified